Construction and application of Anhui Unicom enterprise big data platform - Tao WU; Tao LIU; Bin WANG (Dianxin kexue)
The challenges and opportunities faced by Anhui Unicom of big data construction,and the experience of Anhui Unicom rapidly constructing B+O convergent smart operation platform which realized multi-dimensional and multi-level fusion management of cross-domain platform were summarized.In addition,the customer off-grid prediction was also deeply studied by Anhui Unicom.Achieving the off-grid prediction model through the big data platform which made the precision ratio get 90% and the recall ration get 9%.On the other hand,the big data platform has been popularized to other departments by integrated applications,such as,user awareness enhancement etc.Internal operation efficiency was improved and NOC (network operations center) was transformed to SOC (service operations center).